Main directions in combining digitization and geoinformation methods for supporting mining production - S. V. Kornilkov; P. А. Rybnikov; L. S. Rybnikova (Известия высших учебных заведений: Геология и разведка, 2025)
Background. The use of digital twins, created by combining digital models and geoinformation systems, enables a comprehensive description of situations that arise during mining operations. This facilitates informed management decisions and ensures safe and efficient management of mining operations. Aim. Justification of approaches to the creation of digital twins of mining production, which accompany mining operations. Methods. A literature search and review; generalization of the accumulated experience in constructing digital twins of hazardous processes to predict the development of gas dynamic phenomena; control over ore quality and drilling and blasting processes; substantiation of hydro geochemical monitoring and interpretation of its results over prolonged periods using numerical hydrogeomigratory model. Results and discussion. The application of a numerical hydrogeological model as a digital twin confirmed the feasibility of analyzing the results of monitoring and digital modeling for supporting decision making at each stage of quarry development under the action of various factors. The results obtained indicate the prospects of the proposed approach to managing complex hydrogeological and mining systems. Conclusion. The combined use of digital twins and geoinformation monitoring data on hazardous phenomena and processes and their further analysis contributes to increasing the efficiency of mining production.